IMPLEMENTATION OF THE CHARACTER EDUCATION IN SD INPRES 48 MARIAT IN SORONG REGENCY - Asri Ika Dwi Martini; Yusuf Hadi Yudha; Etty Sofyatiningrum; Rahmi Rivalina; Nur Listiawati; Relisa Relisa (Jurnal Pendidikan Karakter, 2021)
Abstract: The research aims to provide an overview of the implementation of the Character Education program in solving some character problems faced by SD Inpres 48 Mariat. The specific aims are to take advantage of the best practice of the implementation of character education. This is a case study with a purposive selection of school. The respondents are the school principal, teachers, and students. Referred to the qualitative approach like this research, it used inductive reasoning in the analysis of the data. Data collection was carried out through focus group discussions, interviews, questionnaires, and observation. Data analysis used inductive technique. The result describes that the leader of the school, with support from the teachers, make the brand of the school and its activities. The ability of the leader to build good networks with other institutes and organizations support the ecosystem of the school. The five main values and reading literacy activities were already entrenched. The branding of the school function as a roadmap in the implementing of character education in the school. Keywords: Character Education, educational ecosystem, school branding, role models, networks.